Modelling and investigation of the pneumo-olfactory function of humans - Vladimir Kulish (2008)
Our previous studies show that the lung diffusing capacity - the parameter characterizing alveolar (gas exchange) performance - depends on the effective diffusivity of the alveolar region, morphology of the domain (boundaries between the domain constituents, red blood cell distribution, etc.), and the initial conditions imposed on the alveolar region. These initial conditions can significantly vary depending on the flow conditions in the conductive zone of the respiratory duct and the physical properties of the duct itself. Thus, for instance, the presence of solid micro-particles or other volatile components in the breathing air can affect the alveolar performance. Therefore, a numerical simulation of the "two-phase" air flow is necessary in order to determine the entrance conditions in the alveolar region. In order to perform a numerical simulation of the "two-phase" air flow, one has to know the outside breathing conditions - for instance, chemical components entering the respiratory duct. 1. Diagnostics of diffusion limited respiratory diseases. 2. To study the impact of the second phase present in the air on the respiratory function. 3. Pneumo-olfactory studies (modeling). 4. To develop a mathematical model and algorithm of the human olfactory function, including smell perception and recognition. 5. Side-products of the project.